PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA GAS ELPIJI 5,5 KG (NON SUBSIDI): Survei pada Pelanggan di CV. Jectendra Jaya di Desa Sukaraja Kab. Tasikmalaya - Angelita Jectendra (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The objectives of this study was to determine and analyze price, promotion and purchasing decisions on Elpiji Gas 5,5 Kg at CV. Jectendra Jaya Sukaraja Tasikmalaya and the influence of price and promotion on purchasing decisions Elpiji Gas 5,5 Kg at CV. Jectendra Jaya Sukaraja Tasikmalaya. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the customers of Elpiji Gas 5,5 Kg at CV. Jectendra Jaya Sukaraja Tasikmalaya, with the sampling technique using the censuss sampling method, where the survey was conducted to the customers on Elpiji Gas 5,5 Kg at CV. Jectendra Jaya Sukaraja Tasikmalaya. The data analysis technique used is multiple regression analysis. The results of this test prove that price and promotion simultaneously have a significant effect on purchasing decisions on 5.5 Kg LPG at CV. Jectendra Jaya Sukaraja Tasikmalaya. Likewise, partially price and promotion have a significant effect on purchasing decisions on 5.5 Kg LPG at CV. Jectendra Jaya Sukaraja Tasikmalaya.